Redox proteomics identification of oxidatively modified hippocampal proteins in mild cognitive impairment: Insights into the development of Alzheimer's disease - Butterfield, D. Allan; Poon, H. Fai; St. Clair, Daret; Keller, Jeffery N.; Pierce, William M.; Klein, Jon B.; Markesbery, William R. (Neurobiology of disease, 2006)
Mild cognitive impairment (MCI) is generally referred to the transitional zone between normal cognitive function and early dementia or clinically probable Alzheimer's disease (AD). Oxidative stress plays a significant role in AD and is increased in the superior/middle temporal gyri of MCI subjects. Because AD involves hippocampal-resident memory dysfunction, we determined protein oxidation and identified the oxidized proteins in the hippocampi of MCI subjects. We found that protein oxidation is significantly increased in the hippocampi of MCI subjects when compared to age- and sex-matched controls. By using redox proteomics, we determined the oxidatively modified proteins in MCI hippocampus to be α-enolase (ENO1), glutamine synthetase (GLUL), pyruvate kinase M2 (PKM2) and peptidyl-prolyl cis/ trans isomerase 1 (PIN1). The interacteome of these proteins revealed that these proteins functionally interact with SRC, hypoxia-inducible factor 1, plasminogen (PLG), MYC, tissue plasminogen activator (PLAT) and BCL2L1. Moreover, the interacteome indicates the functional involvement of energy metabolism, synaptic plasticity and mitogenesis/proliferation. Therefore, oxidative inactivation of ENO1, GLUL and PIN1 may alter these cellular processes and lead to the development of AD from MCI. We conclude that protein oxidation plays a significant role in the development of AD from MCI and that the oxidative inactivation of ENO1, GLUL, PKM2 and PIN1 is involved in the progression of AD from MCI. The current study provides a framework for future studies on the development of AD from MCI relevant to oxidative stress.